Wear Performance of Bionic Dimpled-Shape Pistons of Mud Pump - Xuejing Cheng; Tianyu Gao; Shaofeng Ru; Qian Cong (Advances in Materials Science and Engineering)
The piston is one of the parts that most easily become worn out and experience failure in mud pumps for well drilling. By imitating the body surface morphology of the dung beetle, this paper proposed a new type (BW-160) of mud pump piston that had a dimpled shape in the regular layout on the piston leather cup surface and carried out a performance test on the self-built test rig. Firstly, the influence of different dimple diameters on the service life of the piston was analyzed. Secondly, the analysis of the influence of the dimple central included angle on the service life of the piston under the same dimple area density was obtained. Thirdly, the wear of the new type of piston under the same wear time was analyzed. The experimental results indicated that the service life of the piston with dimples on the surface was longer than that of L-Standard pistons, and the maximum increase in the value of service life was 92.06%. Finally, the Workbench module of the software ANSYS was used to discuss the wear-resisting mechanism of the new type of piston.